NILAI-NILAI PENDIDIKAN MULTIKULTURAL KH. FAQIH MASKUMAMBANG DAN KH. HASYIM ASY’ARI DALAM KITAB SYARH HAZZI RU’US - M. Rofiud Darojat; M. Jamhuri; Saifulah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Islamic boarding school scholars with the treasures of books they gave birth to, are a valuable legacy in their role in building a society based on awareness of multicultural values. This study uses qualitative research methods and library research types that collect all information through the literature on the educational values ​​of KH. Faqih Maskumambang and KH. Hasyim Asy'ari. Islamic teachings already contain the values ​​of multicultural education. Islamic teachings not only teach about religious procedures and worship guidelines. He teaches how to be religious by worshiping God and socializing with fellow human beings. There are five values ​​of multicultural education implemented by KH. Faqih Maskumambang and KH. Hasyim Asy'ari. among others: 1) Living in Difference; 2) Mutual Trust; 3) Mutual Understanding; 4) Mutual Respect; 5) Open in Thinking.